Geographic mapping and spatiotemporal patterns of tuberculosis in Libya within ten years' period (2015 to 2024) - Daw, Mohamed Ali; El-Bouzedi, Abdallah H.; Abumahara, Saleh Ali; Najjar, Abdurrahman Khalifa; Ben Ashur, Nouri R.; Grebi, Alaa; Dhu, Amnnh Mohammed; Alkarghali, Ali Fathi; Mohammed, Shahid Husayn; Miftah, Raja Khalid; abdulsamad, Najmuldin abdulbasit; Elbasha, Mohammed Saad; et al. (Frontiers in Epidemiology, 2025)
IntroductionTuberculosis(TB) is still a serious problem with a remarkable global impacts particularly within developing countries such as Libya. According to World Health Organization (WHO) global report, the country is considered a moderate TB burden with incidence of 40 per 100,000 in 2011. Geographic epidemiology has been considered an important tool in preventing TB in large countries. In this study, we intended to identify the geographic and spatiotemporal patterns of the TB incidence rate in Libya between 2015 and 2024.MethodsA cross-sectional retrospective analytical study was conducted within ten years on the data reported through the National TB surveillance system. The data on all TB cases reported from 2015 to 2024 by municipality and region was abstracted. Choropleth maps were drawn showing the TB case notification rates (CNR) per 100,000. Local Moran's I was performed to identify the spatial variations of the disease and temporal and Spatiotemporal analyses were employed in all instances.ResultsDuring the entire study period, 26,478 TB cases were reported from all 22 municipalities in Libya with an annual rate of 40.29/100,000 (95% CI: (40.229 ± 9.01). The highest incidence was reported in 2015 and the lowest one in 2024. Males were significantly reported more than females among notified TB cases, (P < 0.001). The highest CNR was reported in the Eastern region followed by Western and Southern regions. The geospatial distribution of reported cases of TB varied greatly within the provinces and during the study period. There was evident variability throughout the country and over time. High-rate and low-rate clusters were predominantly distributed in the periods. High clusters were concentrated northeast and northwest, though low-level clusters were mainly located in the middle and the southern region of the country.ConclusionThe results of this study provided clear insights into the geographic and spatiotemporal mapping of TB in Libya. There was an overall decreasing trend in TB CNR from 2015 to 2024 parallel with high-risk and low-risk areas. This information should allow the decision-making personnel to implement proper policies to combat TB at national and regional levels.